Computerization level and development of the open systems concept in banking sector in Türkiye - Saker, Haluk (My University, 1994)
unknown
Keywords: Banka ve bankacılık; BİLGİSAYAR,BANKACILIK’TA; Ekonomi; Finansman ekonomisi